Viability of CLIGEN in the climatic conditions of Paraná state, Brazil Viabilidade do CLIGEN para as condições climáticas do estado do Paraná, Brasil - João H. Caviglione; Ines C. de B. Fonseca; João Tavares Filho (Revista Brasileira de Engenharia Agrícola e Ambiental)
Studies on hydrology, agro-meteorology, soil loss and climate change scenarios depend on weather information, which may not be available. Weather generators, such as the CLIGEN, can synthesize daily climate series statistically similar to the observed data. The objective of this study was to evaluate the CLIGEN in generating series in the climatic conditions of Paraná, Brazil, which show transition between Cfa and Cfb climates. Observed data from 20 weather stations from 1975 to 2009 were compared with synthetic series generated with the same number of years. Mean and standard deviation of the number of wet days, daily precipitation, normalized storm peak intensity, solar radiation, maximum and minimum temperatures and dew point were analysed. The coefficient of determination was less than 0.91 in two stations.Under the evaluated conditions, the CLIGEN showed restrictions to simulate the normalized storm peak intensity and, for the remaining variables, it was shown to be viable to synthesize daily climate series statistically similar to those in the observed data. Os estudos de hidrologia, agrometeorologia, perda de solo e de cenários de mudança climática, dependem de informações climáticas passíveis de não estar disponíveis. Os geradores climáticos como o CLIGEN, podem sintetizar séries climáticas diárias estatisticamente semelhantes aos dados observados. O objetivo foi avaliar o CLIGEN na geração de séries climáticas nas condições do Paraná, Brasil, que apresenta transição entre os climas Cfa e Cfb. Dados observados de 20 estações meteorológicas entre 1975 e 2009 foram comparados com séries sintéticas geradas com o mesmo número de anos. Analisaram-se médias e desvios padrão do número de dias com chuva, precipitação diária, intensidade máxima de precipitação normalizada, radiação solar, temperatura máxima, mínima e do ponto de orvalho. O coeficiente de determinação foi inferior a 0,91em duas estações; nas condições avaliadas o CLIGEN apresentou restrições na simulação da intensidade máxima de precipitação normalizada e, para as demais variáveis avaliadas, mostrou-se viável para sintetizar séries climáticas diárias estatisticamente semelhantes aos dados observados.